Pelatihan Peningkatan Kemampuan Guru SMP IT Insan Kamil Cikarang Dalam Melakukan Evaluasi Pembelajaran Menggunakan Computer Base Test (CBT) - Miharja, Muhammad Najamuddin Dwi; Edora, Edora; hadikristanto, Wahyu; Andika, Sophian; Herol, Herol (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
This community service program aims to improve the ability of IT Insan Kamil Cikarang Middle School teachers in conducting learning evaluations using the Computer-Based Test (CBT). Teachers will be given training and an introduction to CBT and given practice to create questions and enter them into the CBT platform. The training method used is a competency-based training approach using demonstration methods and hands-on practice in learning. The results of this training indicate an increase in teacher competency in designing, developing, and implementing information technology-based learning evaluations. It is hoped that this program can increase effectiveness and efficiency in learning evaluation, as well as increase student motivation in learning. Challenges that need to be overcome include the lack of understanding and use of technology by teachers and students, and the need for the right approach in implementing CBT. This program is expected to provide greater benefits for teachers and students.